The climate-related risk profile of the energy-intensive and natural resource-based industries : Evidence from 2020–2023 - Månberger, André; Bauer, Fredric ; 0000-0001-8231-2099; Nilsson, Lars J ; 0000-0003-3403-9491 (Cleaner Engineering and Technology, 2025)
This study investigates the perception and understanding of climate-related risks among six energy-intensive and natural resource-based industry (ENRI) sectors using data from the CDP survey from 2020 to 2023. ENRI sectors, including fossil fuels; cement and concrete; chemicals; metallic smelting; refining; and forming; metallic mineral mining; and pulp and paper mills, are exposed to significant climate-related risks due to their capital-intensive activities and long investment cycles. Our analysis confirms that ENRI firms identify and report more climate-related risks with higher estimated impacts compared to other firms in some risk categories, indicating higher awareness. However, ENRI firms tend to prioritise risks with high impact and high likelihood, and likely underestimate the uncertainty and financial impacts of climate-related risks, such as stranded assets. The study highlights the need for improved climate risk governance. Investors and voluntary disclosure initiatives should encourage firms to assess and report uncertain and high-impact risks, using explorative scenarios to overcome biases. Policymakers must enhance the credibility of climate policies by implementing comprehensive measures to support industrial transformation and stricter guidelines for climate-related risk disclosure. Understanding ENRI firms' perspectives on risks is crucial for informing policy and investment decisions to ensure alignment with net-zero targets. Future research should explore factors influencing risk perception, mitigation strategies, and business opportunities, and examine firms' processes for identifying and managing climate-related risks.
Keywords: Decarbonisation; Industrial transformation; Climate-related risk; Transition risk; Uncertainty